Comparative chloroplast genomes and phylogenetic analysis of six Periploca species from China provide insights into the distinction of members of this small medicinal genus - Shuai, Tian; Li, Qianli; Long, Jinlan; Jiang, Xiaoqi; Wei, Linling; Ding, Ning; Zhou, Wei; Wu, Zhikun (Frontiers in Plant Science, 2025)
IntroductionThe genus Periploca L. (Apocynaceae) comprises approximately 17 species worldwide and possesses considerable medicinal value. However, owing to morphological similarities in vegetative organs, specimens and living plants usually lacking flowers and fruits are difficult to determine to species level posing challenges for its proper medicinal utilization.MethodsIn this study, we sequenced and assembled the complete chloroplast (cp) genomes of five Periploca species (P. chrysantha, P. forrestii, P. calophylla, P. floribunda, and P. tsiangii). By combining the new data with the published cp genome of P. sepium and 22 additional Apocynaceae cp genomes from NCBI, we conducted a comparative analysis of all recognized Periploca species from China and their closely related taxa to elucidate their phylogenetic relationships.ResultsThe cp genomes of Periploca exhibit a typical quadripartite structure, with lengths ranging from 153,513 to 154,140 bp and a GC content of 38.1–38.2%. These cp genomes encode 132 genes, including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Single-nucleotide repeats (A/T) varied among the six species, with forward and palindromic repeats being the dominant long repeat types. We identified 60 long repeat sequences and 55–73 simple sequence repeats, with A/T repeats being the most abundant. Sequence conservation was highest at the SC/IR boundary, while the LSC and SSC regions contained the most highly variable regions. Ten highly variable regions (including trnK-UUU-rps16, rps16-trnQ-UUG-psbK, rpoB-trnC-GCA-petN, ycf3-trnS-GGA-rps4, trnT-UGU-trnL-UAA, ndhC-trnC-ACA, ycf1-ndhF, ndhF-rpl32, ndhA, and rps15-trnN-GUU) were identified based on nucleotide diversity and verified by Sanger sequencing, serving as potential molecular markers for the identification of Periploca and related genera. Phylogenetic analyses of the complete cp genome sequences successfully distinguished the six Periploca species and revealed the evolutionary relationships among them.DiscussionThese findings enrich the genetic resources for Periploca, providing insights into molecular identification and phylogeny, and fostering proper medicinal application.